Complete mitochondrial genome of Triplophysa robusta (Teleostei: Cypriniformes: Balitoridae). (3rd May 2016) - Yan, Pengfei; Li, Jiuxuan; Ma, Qingzhan; Deng, Yuanping; Song, Zhaobin
Abstract: The complete mitochondrial genome of the Triplophysa robusta has been determined in this study. It is 16, 572 bp in size and consists of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one non-coding control region (D-loop). The overall base composition of the heavy strand of the T. robusta mitochondrial genome was A: 28.20%, T: 28.27%, C: 25.37%, and G: 18.16%. The total length of the 13 protein-coding genes was 11, 428 bp. Analysis of the genes indicated the high genetic variability among Triplophysa species.